Stereotactic drainage of empyema of the cavum septi pellucidi et vergae - Saryyeva, Assel; Nakamura, Makoto; Capelle, Hans-Holger; Krauss, Joachim K. (Stereotactic and functional neurosurgery, 2012)
Background: Persistent midline ventricular cavae may only rarely cause clinical symptoms. Exceptionally, empyemas may develop in these cavae. Optimal treatment has been defined only poorly so far. Methods: Here, we report successful treatment of a bacterial empyema in the cavum septi pellucidi et vergae due to sphenoid sinus sinusitis in a 36-year-old woman by stereotactic puncture and drainage of the empyema and long-term administration of antibiotics. Results and Conclusions: Stereotactic puncture and drainage accompanied by antibiotic therapy result in beneficial outcome in the long term. Transcallosal interhemispheric approaches and free-hand techniques should be discouraged since, according to previously published reports, they may result in severe morbidity or mortality in this condition.